Study of the Compressive Strength of Concrete with Partial Replacement of Recycled Coarse Aggregates - Vu, X. H.; Vo, T. C.; Phan, V. T. (Engineering, Technology & Applied Science Research, 2021)
This paper presents a study on the compressive strength of concrete using recycled aggregates. The concrete was designed to have a 25MPa compressive strength and an 8cm slump. The rates of replacing natural aggregates with recycled coarse were 0%, 10%, and 20%. The test samples were compressed to determine their compressive strength value after 7, 14, and 28 days of curing. The results showed that the concrete slump did not change effectively at a 10% replacement rate. When using 20% recycled aggregates, the concrete was too hard and the homogeneity of the concrete mixture could not be guaranteed. The compressive strength slightly decreased using 10% of recycled aggregates and decreased significantly using 20%. Therefore, 20% of recycled aggregate replacement is not suitable. The results showed that using recycled aggregates at a rate of 10% is optimal.